2014
DOI: 10.1007/s00253-014-5900-7
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens-mediated genetic transformation of haptophytes (Isochrysis species)

Abstract: Isochrysis galbana and Isochrysis sp. are economically important microalgae from the division of haptophytes. Here, we report Agrobacterium-mediated stable DNA transfer into their nuclear genomes. Initial studies were performed to standardize co-cultivation media and determine the sensitivity of the microalgae to selective agents. Up to 1 mg/ml of the antibiotic hygromycin did not inhibit growth, whereas both the haptophytes bleached in artificial seawater (ASW) medium containing micromolar concentrations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 40 publications
0
23
0
1
Order By: Relevance
“…Several microalgal species were transformed by Agrobacterium , including Chlamydomonas (Kumar et al, 2004 ; Pratheesh et al, 2014 ), as well as other algae of biotechnological value, such as H. pluvialis (Kathiresan et al, 2015 ), Schizochytrium (Cheng et al, 2012 ), Isochrysis galbana , and Isochrysis sp. (Prasad et al, 2014 ).…”
Section: Nuclear Transformationmentioning
confidence: 99%
“…Several microalgal species were transformed by Agrobacterium , including Chlamydomonas (Kumar et al, 2004 ; Pratheesh et al, 2014 ), as well as other algae of biotechnological value, such as H. pluvialis (Kathiresan et al, 2015 ), Schizochytrium (Cheng et al, 2012 ), Isochrysis galbana , and Isochrysis sp. (Prasad et al, 2014 ).…”
Section: Nuclear Transformationmentioning
confidence: 99%
“…Agrobacterium has been used extensively to 315 transfer DNA to eukaryotic algae in the green algal lineage with subsequent chromosomal integration (29)(30)(31)(32). In contrast, to our knowledge, the only other example beyond our results of using A. tumefaciens to deliver DNA maintained as an episome in the recipient was with yeast (14).…”
Section: Discussionmentioning
confidence: 91%
“…We also observed that A. tumefaciens could perform interdomain conjugation with P. tricornutum resulting in establishment of episomes in the recipient when the cargo plasmid contained a centromeric maintenance sequence. Agrobacterium has been used extensively to 315 transfer DNA to eukaryotic algae in the green algal lineage with subsequent chromosomal integration (29)(30)(31)(32). In contrast, to our knowledge, the only other example beyond our results of using A. tumefaciens to deliver DNA maintained as an episome in the recipient was with yeast (14).…”
Section: Discussionmentioning
confidence: 91%